Religion in schools - Merino, Noel (Introducing issues with opposing viewpoints, 2012)
This book is a collection of articles in which authors debate whether public schools have been overly sanitized of religion, whether evolution should be taught without alternatives, and whether religious holiday activities in schools must be educational and inclusive.